Fibroblast Growth Factor Receptor Inhibition in a Model of Multiple Sclerosis: Immunological Effects in vivo and in vitro - Böttiger, Gregor Wolfram; Justus Liebig University Giessen (My University, 2024)
The fibroblast growth factor (FGF) signaling pathway, fundamental to vertebrates, is involved in embryogenesis, a plethora of developmental processes and disease states. Beyond this, the pathway is also a major regulator of tissue homeostasis and is essential for the integrity, regeneration, and repair of the central nervous system (CNS). Its importance in pathological conditions is underscored by accumulating evidence indicating that it plays a critical role in the pathogenesis of both multiple sclerosis (MS) and experimental autoimmune encephalitis (EAE). Interestingly, FGF receptor (FGFR) signaling in T cells and microglia is primarily modulatory and contingent upon the activation status of these cells. This is particularly relevant in diseases such as EAE and MS, where the microenvironment and disease phase are crucial to the drastic temporal change of lesions. Based on our recent studies, we hypothesized that FGFR inhibition would lead to a reduction in inflammation and immune cell activation and proliferation. To investigate this, we used an in vitro and in vivo approach. In vitro, we utilized two cell types, human CD4+ T cells (Jurkat cells) and mouse microglia (SIM-A9 cells), and three drugs: the multi-kinase inhibitor dovitinib, the non-specific FGFR1/2/3 inhibitor fexagratinib, and the selective FGFR1/2/3 inhibitor infigratinib. The study examined in vivo how infigratinib affected the immune cells both in the blood and in the spleen of mice with EAE. The study showed that in vitro, all three drugs reduce the proliferation of both cell types. However, they had varying impacts on cytokine release, FGFR surface expression, and intracellular signaling pathways. In vivo, infigratinib demonstrated significant effects on immune cells particularly during the acute phase of EAE, when administered preventively. Infigratinib reduced the proportion of T and B cells in the spleen, altered the balance of CD4+ and CD8+ T cells, and increased the number of innate immune cells. The data also suggested that FGFR inhibition affects the ERK, Akt, and pP38 pathways in a cell- and substance-specific manner, which itself may have differential context-specific effects on inflammation and tissue repair. The present work discusses the potential role of FGFR autoregulation, ligand-receptor interactions and cytokine composition in the modulation of the immune response in MS. It proposes the notion of immunostimulatory modulation by FGFR inhibition, which may inhibit the activation and proliferation of peripheral adaptive immune cells and promote cells of the regulatory parts of the adaptive immune system as well as regulatory cells of the innate immune system. In doing so, it could actually reduce inflammation and aid tissue repair in MS by reducing pathological and increasing beneficial immune cells. It is thus postulated, that FGFR inhibition has both anti-inflammatory but also pro-inflammatory properties, stimulating regulatory parts of the immune system. In conclusion, the microenvironment in inflammatory or autoimmune states plays a pivotal role in modulating FGFR signaling in immune cells, including their proliferation and/or activation. For the understanding of this modulation as well as for the understanding of the immunologic pathophysiology of demyelinating diseases, the downstream pathways of FGFR are highly important. However, further research is needed to overcome the limitations of the present study and to explore the specific implications of FGFR inhibition on different immune cells and their modulatory effects on inflammation and the CNS environment in MS.
Keywords: Multiple Sklerose; EAE; FGFR; Neuroimmunologie; Neuroinflammation; FGF; Demyelinierung; Encephalomyelitis; FGFR Inhibition; ddc:610